Perancangan Apartemen Green City Bekasi Dengan Tema Green Nature Dengan Pendekatan Konsep Green Building di Kawasan Bekasi Town Square - Ahmad Aguswin; Arman Bagastama (DPPM Universitas Pelita Bangsa, 2022)
The large number of people and their activities have an impact on increasing the need for shelter, the need for land for residence is even less so because of the vertical housing development. indispensable, but the construction of vertical housing can cause problems, one of which can cause Global Warming or global warming, therefore the design of the apartment must be aware also to protect the environment, the purpose of this study is to find out how necessary the construction of apartments with the green building concept approach and with the theme of green nature and using descriptive, documentative, comparative methods, with the design of apartments with the concept of green building so that the construction of vertical housing or apartment can solve the problem of residential needs in the City Bekasi, can accommodate many dwellings in a narrow area, and also by designing the concept of green building apartments that also take care of the environment around him and can also reduce the effects of global warming, his conclusion The need for residential housing in the area of Bekasi City is increasing but the land for housing is also getting smaller and therefore vertical housing development is really needed for the Bekasi City area. In designing a building with the concept of green building we must meet several variable requirements, namely appropriate land use, energy efficiency and conservation, water use efficiency, material source & cycle, indoor air quality & air comfort, building environmental management. Keywords: Design, Apartment, Green Building